Affective Disorders in The Elderly: The Risk of Sleep Disorders - Eni Folendra Rosa; Nelly Rustiaty (Intelektual Pustaka Media Utama, 2018)
The purpose of this study is to look at the relationship of sleep disorders to the incidence of affective disorders. In addition, assess whether the relationship remains significant after controlled variable bullies that also affect the occurrence of sleep disorders and or affective disorders in elderly. Observational study with unmatched case control study design. Individual population age 60 years or older, sampling probability proportional to size, consist of case group that is experiencing sleep disturbance (n=165) and control group (n=330). Respondent sleep disturbance affective disorder 23.6%. There is a significant relationship of sleep disorders to affective disorders. Sleep disorders at risk 2.47 times affective disorder. Sleep disorders can be insomnia, awakening at night or waking up too early which can lead to psychological disorders such as psychological disorders such as anger, unstable emotions, sadness, distress, anxiety is also a physical disorder such as pain in the body. If not immediately addressed can continue to occur depression and even threaten psychiatric disorders. Further research needs to be done to overcome sleep disorders in the elderly.